Research of Uplink Discontinuous Transmission Control Method of TD-SCDMA System - Wenwen Li; Chenguang Jin; Bo Wu (Dianxin kexue)
Due to discontinuous transmission characteristics, uplink DTX could bring benefits such as terminal power-saving and interference reducing to TD-SCDMA system. During the existing standard, the default state of uplink DTX is on, without corresponding off mechanism, which may deteriorate the performance and reliability of communication system. In order to solve the uncontrollable problem of uplink DTX state, fill the blank of existing standards, and meet the operation demands of communication system, three kinds of on-off methods were introduced, and their implementation effects were discussed from six dimensions.